(untitled) (BIRDEM Medical Journal, 2012)
Obesity is a global health problem including bangladesh resulting in major morbidity and premature death. The causes of this epidemic are complex and multifactorial, but fundamentally lead to an excess calorie intake over energy expenditure. Modern lifestyles, incorporating altered eating patterns, access to cheap, highly palatable, energy-dense yet nutritionally poor foods, sedentary habits and laborsaving devices, have hugely accelerated the problem during last few years. Till date safe and efficacious drug therapies remains unmet. The two drugs for the long-term treatment of obesity, Orlistat and Sibutramine, provide only modest weight-loss benefits and are associated with high attrition rates owing to side effects. Currently neuroendocrine control of energy homeostasis and major pharmacological treatments for obesity in the pipeline. The discovery of leptin and other gut hormones as major neuroendocrine regulators of bodyweight is leading the way to the development of attractive therapeutic approaches to the long-term manipulation of energy homeostasis in favor of appetite reduction and weight loss. It is hoped that this may be associated with a relative paucity of central or unexpected side effects. The rest of this article will concentrate on these therapeutic strategies. Still shortcomings of medical treatment encouraged the Barriatric surgery specially for morbid obese subjects. Though many advantages are ascribed including remission and improvement of Type 2 diabetes mellitus, long term metabolic and nutritional effects still remains questionable. Comparative data among different procedures of Barriatric surgery are also insufficient. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12384 Birdem Med J 2011; 1(1): 26-29